Desenvolvimento de marcadores moleculares espécie-específicos para a identificação de Eucalyptus - Rivera-Jiménez, Hernando Javier [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The forest-breeding program in Brazil has the general objective of providing most adapted plants to different environments for various Brazilian regions, for fulfilling timber demands meant for multiple uses in the country. One of the main problems found in different forest breeding programs are the difficulty to identify the different species and hybrids. The use of molecular biology techniques in plant breeding programs is found very effective in the optimization of the time and the direction of these programs, particularly among those plants of the same subgenus. The process of selection and hybrid plants selected for planting in most cases; significantly increase the gain in terms of production and adaptability. The use of molecular markers to characterize the molecular variability of forest species has revolutionized genetic analysis in recent years. The bulk segregant analysis (BSA) is a technique used to identify molecular markers linked to monogenic, dominant or recessive characters. BSA technique in combination with Amplified Fragment Length Polymorphisms (AFLP) technique is an efficient methodology for the detection of polymorphism from genomic restriction fragments through PCR amplification; which helps in analyzing large number of loci for testing without the need for previous information of their sequence in respect to their dominance and reproducibility. The most recent and promising applications of molecular biological methods for the detection of small DNA fragments as identification tool and constituency of species in plants and animals is called DNA barcode. The use of barcode DNA sequence is useful for grouping data and analyzing jointly in order with ease of amplification and sequencing and quality of sequence discriminatory power of the marker.
Development of species-specific markers for the identification of Eucalyptus
Keywords: Eucalyptus; AFLP; BSA; DNA Barcode; Species discrimination